2020
DOI: 10.1016/j.ijantimicag.2020.106152
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of generic meropenem products in combination with colistin in carbapenemase-producing Klebsiella pneumoniae experimental osteomyelitis

Abstract: Highlights-Carbapenemase-producing Enterobacteriaceae are emerging multidrug-resistant bacteria responsible for invasive infections, including osteomyelitis.-Although optimal antibacterial regimen remains undefined, most experts recommend a combination of two active agents, including meropenem if MIC < 8 mg/L -We compared the efficacy of five meropenem products in combination with colistin, in vitro, and in a rabbit model of carbapenemase-producing Enterobacteriaceae osteomyelitis.-We found no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…19 The results of study are supporting the Japanese published data showing 60% clinical efficacy of colistin therapy against multidrug-resistant KP infection. 20 Another study revealed 70% imipenem resistance among KP isolates which is almost similar to our observation of 74% resistance to imipenem. 21 In the present era of increasing AMR perhaps colistin being the only choice left for treatment of such MDR and XDR pathogens.…”
Section: Miscellaneoussupporting
confidence: 89%
“…19 The results of study are supporting the Japanese published data showing 60% clinical efficacy of colistin therapy against multidrug-resistant KP infection. 20 Another study revealed 70% imipenem resistance among KP isolates which is almost similar to our observation of 74% resistance to imipenem. 21 In the present era of increasing AMR perhaps colistin being the only choice left for treatment of such MDR and XDR pathogens.…”
Section: Miscellaneoussupporting
confidence: 89%
“…Hagihara et al, found that meropenem plus amikacin was effective against KPC-, IMP-and OXA-48-producing K. pneumoniae infections, except for NDM type carbapenemase producing (13). Also, the combination of meropenem plus colistin was found to be bactericidal against a KPC-producing K. pneumoniae experimental osteomyelitis in rabbits (14). Several studies have suggested fosfomycin combination with other antimicrobials to be explored because of its in vitro activity.…”
Section: Introductionmentioning
confidence: 99%